Marketing control and performance in early-growth companies - Boag, David A. (Journal of Business Venturing, 1987)
This article examines the relationship between market performance and marketing control systems used by early-growth electronic component and instrument manufacturers. Essentially, “marketing control” means keeping things on track. Long pushed aside by the excitement of planning and organizing business ventures, controlling operations, particularly marketing operations, has received little attention. This is regrettable because control is the only mechanism which ensures that resources are allocated efficiently and that strategic objectives are met. Also, for the early-growth high tech company, which is already in a state of flux, developing an appropriate marketing control system is essential to its ability to meet and respond to the recurring challenges brought about by the pace at which change is occurring. In this article the author examines the issue of marketing control from a theoretical as well as an empirical perspective. First, the author presents a framework for evaluating the marketing control system within a company. The core of the framework presents the essential elements of marketing control: feedback and corrective action. Bounding the core is: 1.1. The Formal Marketing Organization. Delimits the company's capability to enact the control processes.2.2. Marketing Culture. The subjective, interpretive aspect of organizational life, which determines what control components and marketing structure are valued in the company. The framework is used to analyze the marketing control systems of 20 early-growth high tech manufacturing companies. Four hierarchical configurations of the control system elements are identified and the companies assigned to one of the following configurations: 1.I. seeking some sales.2.II. making good on sales.3.III. seeking profitable sales.4.IV. making profitable sales. Four companies possessed none of the elements of control. There were merely operations which produced results. As a consequence the companies were judged to be generally unsuccessful in focusing their resources on the markets that they wished to serve. In addition, the market performances of these firms, relative to others in the sample, were poor. Ten Stage II companies, in their attempts to expand sales and to remedy logistical problems associated with making deliveries on sales, had developed formal sales departments. Unlike the four companies which were placed in Stage III, these companies put little emphasis on the financial accountability of sales and marketing. Consequently, their abilities to evaluate or steer profit performances mitigated against their achieving high levels of market performance. Only two companies were judged sufficiently different from other companies to warrant placement in Stage IV. These companies focused on developing marketing structures and reporting procedures which provided real time feedback on market performances. Because of this, they appeared able to identify market opportunities that were defensible in the long run and in which they could exercise control over profits. In conclusion, the findings indicate that greater control of marketing operations correlates with stronger market performances. When performance is measured in terms of absolute sales, sales growth. cumulative cashflow and profitability, companies with more evolved marketing control systems perform noticeably better than do others in the sample.